Development of Lasem War Teaching Materials in Form Booklet for Learning Local History at SMA Negeri 1 Lasem - Yusuf, Muhammad; Saraswati, Ufi; Ahmad, Tsabit Azinar (Indonesian Journal of History Education, 2022)
This study aimed to describe the needs of teachers and students in learning local history at SMAN 1 Lasem, knowing the development of regional history teaching materials, and understanding the effectiveness of the teaching materials developed. The method used in this study was the research and development method with the pretest-posttest control group design. Data collection techniques used in this study include observation techniques, interviews, questionnaires, document studies, and tests. The results showed that the development of teaching materials in the form of booklets on the local history of the War of Lasem was tailored to the needs of teachers and students and relevant sources. The feasibility of booklet teaching material was seen from the results of validation by material experts in stage I (82.04%) and stage II (84.49%) and media experts in stage I (75.56%) and stage II (78.75%) and teacher responses (87.5%) and students (88%) so that it can be concluded that the booklet-shaped teaching material is suitable for use in learning local history in SMAN 1 Lasem. Using teaching materials in the form of booklets can improve student learning outcomes. The experimental class student learning outcomes (84.6538) were better than the control (78.3571). Therefore, it can be concluded that the teaching materials in booklets are effective for teaching materials used in learning local history in SMAN 1 Lasem.